Barriers to Child Support After Divorce: A Legal Review in the Indonesian Context - Samanta, Silva (Sakina: Journal of Family Studies, 2024)
Child support is one of the legal issues that arise after divorce. Although the law clearly states that child support is a shared responsibility post-divorce, it is not always guaranteed that child support will be fulfilled in accordance with court rulings and applicable laws. One issue that may occur is when the ex-wife obstructs the ex-husband from fulfilling his obligation to provide child support, even denying him access to meet his child. This research aims to describe the views of Civil Law Experts on the obstruction of ex-husbands in providing child support and to explain the legal remedies available for ex-husbands when ex-wives obstruct child support obligations. This research falls under the category of empirical juridical research with a sociological approach. The data sources were obtained through interviews with Islamic Civil Law Experts and supported by relevant laws and literature. The findings of this research indicate that the actions of an ex-wife obstructing the ex-husband from providing child support are not justified, as there is no detailed regulation allowing such obstruction unless it causes harm to the child. The legal recourse available to the ex-husband when his child support obligations are obstructed after divorce is to file a lawsuit for child custody, as stipulated in SEMA No. 1 of 2017.